Effect of Gd0.2Ce0.8O2 Sintering Temperature on Formation of a SrZrO3 Blocking Layer between Y0.16Zr0.84O2, Gd0.2Ce0.8O2 and La0.58Sr0.4Co0.2Fe0.8O3. (13th April 2015) - Wilde, Virginia; Störmer, Heike; Szász, Julian; Wankmüller, Florian; Ivers-Tiffée, Ellen; Gerthsen, Dagmar
Abstract : This study focuses on the microstructural characterization of LSCF(La0.58 Sr0.4 Co0.2 Fe0.8 O3-δ )-GDC (Gd0.2 Ce0.8 O2-δ) and GDC-YDZ (8 mol% Y2 O3 -doped ZrO2 ) interfaces in solid oxide fuel cells (SOFCs) using transmission electron microscopy (TEM). In particular, the influence of the GDC sintering temperature on microstructure evolution is studied. As a result, an interdiffusion layer between GDC and YDZ is observed. In case of lower GDC sintering temperatures (1100 ℃) the YDZ/GDC interface region consists of two different layers with distinct elemental composition. The layer adjoined to the GDC layer is rich in Sr and Zr, indicating SrZrO3 (SZO) formation; the layer adjoined to YDZ is rich in Gd. With higher GDC sintering temperature the Gd-rich layer increases in thickness, whereas SZO formation is reduced. In this case, only disconnected regions of SZO are formed.